Supplementing Blood Diet With Plant Nectar Enhances Egg Fertility in Stomoxys calcitrans - Tawich, Simon K.; Bargul, Joel L.; Masiga, Daniel; Getahun, Merid N. (Frontiers in Physiology, 2021)
Stomoxys calcitrans (stable fly) is a cosmopolitan biting fly of both medical and veterinary importance. Unlike blood feeding related behaviour of stable fly, plant feeding, the fitness value and the S. calcitrans-plant interaction is less understood. Here, we show based on the two chloroplast DNA genes, ribulose bisphosphate carboxylase large chain (rbcL) and the intergenic spacer gene trnH-psbA that field-collected male and female stable flies fed on various plant species. We investigated the fitness cost of plant feeding using Parthenium hysterophorus, one of the plant species identified to have been fed on by the field-collected flies. Supplementation of blood feeding with a flowering P. hysterophorus plant as nectar source enhanced egg hatchability significantly as compared to blood alone, showing the showing the fitness value of nectar supplementation. However, nectar supplementation did not affect the number of eggs laid or longevity of S. calcitrans as compared to flies fed on blood alone. S. calcitrans maintained on sugar alone failed to lay eggs. The various plants stable flies fed on demonstrated chemodiversity with their own signature scent. The behavioral response of S. calcitrans to these signature compounds varied from strong attraction (γ-terpinene) to neutral (linalool oxide). Our study demonstrated that stable flies feed on nectar, blood feeding is necessary for S. calcitrans survival, reproduction, and plant nectar supplementation enhanced larval emergence. Thus, our result has implication in stable fly reproduction, survival, diseases transmission, boosting laboratory colony and the possibility of using plant derived odors for mass trapping of stable fly for instance using γ-terpinene.